Repertório vocal de Dendropsophus microps (Peters, 1872) (Anura, Hylidae) - Toledo, Maysa Hernandes Ricardo [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Os anuros apresentam diferentes tipos de canto, com diferentes funções no contexto social, classificadas por observações de campo e experimentos de playback. No presente estudo descrevemos as vocalizações emitidas por Dendropsophus microps presentes na Serra da Mantiqueira, em Campos do Jordão, São Paulo, Brasil e avaliamos suas funções no contexto social destes anuros por meio de experimentos de playback. Entre outubro a dezembro de 2016 foram gravados 15 indivíduos machos de D. microps (CRC: 21,2 mm – 27,6 mm; Peso: 0,6 g – 1,1 g). Foram analisados 605 cantos e verificada a existência de 3 diferentes tipos: “A”; canto tipo “A fusionado (Af); cantos tipo “B”. Os cantos encontrados formaram 5 tipos de composições: canto simples “A normal”; canto composto “Af”; canto “A” mais curto + “A” mais longo; cantos “A +Af”; canto simples “B”; demonstrando a presença de canto composto na estrutura de vocalização. Com estes cantos foram construídos 5 estímulos de playback. Entre setembro a novembro de 2017 foram gravados 2.009 cantos. A fase do estímulo reuniu 51,4% dos cantos emitidos, sendo o canto “B” o mais emitido. Os estímulos “A”, “Af”, “AA” e “AAf” geraram uma decaída na porcentagem de emissão de cantos “B” e um aumento na quantidade de emissão de cantos “A”, “Af”, “AA” e “AAf”, também ocasionou resposta comportamental de sinalização visual. Foram registrados cinco casos formação de amplexo, oito machos realizando sinalização visual e três combates físicos entre machos de D. microps. Foi registrado série de 4 a 5 cantos “A” durante interações agonísticas. Estudos bioacústicos anteriores com D. microps demonstraram semelhanças nos valores dos parâmetros espectrais do canto de anúncio quando comparados aos indivíduos de Campos do Jordão, porém algumas desatualizações na nomenclatura. Aqui identificamos o canto “B” como canto de anúncio e os cantos “A”, “Af” , “AA” e “AAf” como cantos agressivos. Também foi constatado a presença de comunicação visual adicionalmente a comunicação acústica destes indivíduos. Os resultados encontrados aumentam o conhecimento acerca do canto dessa espécie, podendo ser usados futuramente em outros estudos comportamentais e taxonômicos.

Anurans present different types of calls, with different functions in the social context, classified by field observations and playback experiments. The aim of this study was to describe the vocalizations emitted by Dendropsophus microps present in the Serra da Mantiqueira, Campos do Jordão, Brazil, and evaluated calls functions in the social context by playback experiments in natural conditions. Between october and december 2016, fifteen males of D. microps (CRC: 21.2 mm - 27.6 mm; Weight: 0.6 g - 1.1 g) were recorded. We analyzed 605 calls and verified the existence of three different types: "A" ; "A fused" (AF); “B”. These calls are organized in 5 different compositions: simple call "A"; compoused call "AF"; call "A" shorter + "A" longer; call "A + AF"; simple call "B”, showing the presence of a composed call in the vocalization structure. We built 5 playback stimuli using this compositions. Between september and november 2017, 2,009 calls were recorded. The stimulus stage represented 51.4% of all calls issued, call "B" was the most emitted. The "A", "Af", "AA" and "AAf" stimuli generated a decrease in the percentage of calls "B" issuing and an increase in the issuance of "A","Af", "AA", "AAf”, and also caused behavioral response such as toe troembling visual signaling. Five cases of embracing were recorded, eight males performing visual signaling and three physical combats among males of D. microps. A call series composed by four to five short calls "A" were recorded during agonistic interactions. Previous bioacoustic studies performed with this species showed similarities between spectral parameters values in comparison of Campos do Jordão individuals, but there is some outdated nomenclatures. Other species on studies with playback methodology showed similar behavior such as D. microps in response to coespecific signals. Here we identify the call "B" as the advertisement call and "A", "Af”; "AA", "AAf" calls as aggressive call. It was also verified the presence of visual communication in addition to acoustic communication of these individuals. The results founded here increase the knowledge about the vocalization of this species and can be used in the future in other behavioral and taxonomic studies.
Vocal repertoire of Dendropsophus microps (Peters, 1872) (Anura, Hylidae)
Keywords: Bioacústica; Serra da Mantiqueira.; Anuros; Hilídeos; Experimento de playback; Anurans; Tree frogs; Playback methodology; Bioacustic